The Influence of Behavioral Biases and Islamic Financial Literacy on Investment Decisions of Young Investors in Malaysia - Saiful Bahri; Ahmad Ridhuwan bin Abdullah; Sunarto; Deswita Siti Nurul Aeni; Laila Hasna Risqiya (International Journal of Management, Business, and Social Sciences, 2025)
This study aims to analyze the influence of behavioral bias and Islamic financial literacy on students' investment decisions as a representation of young Muslim investors. An explanatory quantitative approach was used by collecting data through an online questionnaire distributed to 48 students at Universiti Malaysia Kelantan (UMK). Data analysis was carried out using multiple linear regression through SPSS version 27. The results showed that of the three dimensions of overconfidence, only overplacement had a significant positive effect on investment decisions, while overprecision, overestimation, loss aversion, and anchoring bias did not show a significant effect. On the other hand, Islamic financial literacy has the strongest positive influence on investment decisions, indicating that understanding of Islamic financial principles is able to suppress behavioral bias and increase investment rationality. Theoretically, these findings expand the perspective of behavioral finance by including Islamic values as a controlling factor for cognitive bias. Practically, the results of this study provide input for educational institutions and financial authorities to strengthen Islamic financial literacy to form rational, ethical, and sustainable investment behavior among young investors.